Bland nervdroppar, bakterier och screeningar: om medicinskt språk i Svensk ordbok utgiven av Svenska Akademien - Landqvist, Hans; Sköldberg, Emma (LexicoNordica, 2018)
In this paper, we report on a comparative pilot investigation concerning medical language in The Contemporary Dictionary of the Swedish Academy (SO). Challenges posed by how general languages dictionaries treat lemmas commonly used in the field of medicine are identified. We clarify how the field of medicine is presented in the first edition of SO (2009). Comparisons are made between SO and two Swedish specialist Internet resources. The paper is concluded with a discussion of how the field of medicine can be presented in the second edition of SO.